Sublethal effects of acetamiprid and afidopyropen on Harmonia axyridis: insights from transcriptomics analysis - Liang Zhang; Haixiang Lv; Xuchao Li; Hu Wan; Shun He; Jianhong Li; Kangsheng Ma (Ecotoxicology and Environmental Safety, 2023)
Evaluating the sublethal effects of insecticide is crucial for protecting and utilizing natural enemies. In this study, we determined the sublethal effects of acetamiprid and afidopyropen on Harmonia axyridis (Pallas) and explored the potential molecular mechanisms underlying these effects through transcriptomics analysis. The results showed that sublethal concentrations of acetamiprid significantly reduced the adult fecundity and longevity of F0 H. axyridis and decreased the survival time and survival rate of the F1 generation. Sublethal concentrations of afidopyropen prolonged the developmental time of 4th instar larvae in the F0 generation. Additionally, acetamiprid and afidopyropen treatments significantly decreased the predation of H. axyridis. Furthermore, transcriptome sequencing analysis revealed that several P450 and UGT genes expressed differently when H. axyridis were exposed to sublethal concentrations of acetamiprid and afidopyropen, suggesting that the differential expression of detoxifying genes might be involved in the response and detoxification metabolism of acetamiprid and afidopyropen in H. axyridis. Our findings demonstrate that sublethal concentrations of acetamiprid adversely influences the development and predation of H. axyridis, while afidopyropen has limited effects on H. axyridis. These results are helpful for protecting and utilizing natural enemies and guiding the scientific use of pesticides in the field.